Effects Of Discipline, Punishment And Reward On Employee Performance At PT Petrokimia Gresik - Muhammad Kahfi Arya Pratama Wardoyo; Widakdo Danang SWPJ; Setiadevi Shinta (Jurnal Javanica, 2023)
This research was conducted at laboratorium PPK 1 Petrokimia Gresik This study aims to determine the effect of Work Discipline, Punishment, and Reward, on employee performance at laboratorium PPK 1 Petrokimia Gresik, Research data collection techniques used questionnaires.  The result of the t-test and f-test analysis showed that the variable of work discipline (X1) punishment (X2) and reward (X3) had a positive and significant effect on employee performance partially or simultaneously. The R square value of 0,779 indicated that the magnitude of the influence of work discipline, punishment, and reward on employee performance is 77,9% and the remaining 22,1% is influenced by other variable.